Acute presentation of a solitary caecal diverticulum: a case report - Griffiths, Ewen A (BioMed Central, 2007)
INTRODUCTION: Solitary caecal diverticulitis is a rare cause of abdominal pain in Caucasian patients. The condition is often misdiagnosed and only correctly identified on exploration for suspected acute appendicitis. Our aim is to improve awareness of this condition amongst surgical trainees to ensure that its first encounter is not in the operating theatre. We review the role of pre-operative radiological imaging in this condition and the wide and controversial management options are also discussed. CASE PRESENTATION: A 67 years old man was admitted with a 24 hour history of pain in right iliac fossa. A pre-operative diagnosis of acute appendicitis was made but at operation a 2.5 cm inflamed and gangrenous solitary diverticulum of caecum was found. This was treated by right hemicolectomy as there was the suspicion of underlying malignancy. CONCLUSION: Caecal diverticulitis, although rare in the Western population, should be considered in the differential diagnosis of patients complaining of right iliac fossa pain. The surgical approach should be tailored to the clinical scenario but may include conservative management, diverticulectomy, limited ileocaecal resection or right hemicoloectomy.